A REVIEW OF THE USE OF RESTRICTIVE ANTIBIOTICS IN ONE OF THE TEACHING HOSPITALS IN INDONESIA - Munawir; Rakhmat Muzakkir; Riska Ropika; Mukhtasyam Zuchrullah (Jurnal Endurance, 2025)
The irrational use of antibiotics in hospitals can increase bacterial resistance, necessitating monitoring of their usage patterns. This study aims to describe the clinical characteristics of patients and the usage patterns of meropenem and vancomycin antibiotics at Universitas Hasanuddin Hospital. The study employed a retrospective analytical method using secondary data from electronic medical records and antibiotic request forms. The results showed that the majority of meropenem users were adults (61.25%) and the elderly (28.75%), while vancomycin was predominantly used by adult patients. Among meropenem patients, the primary diagnoses were CKD (13.75%) and sepsis (7.5%), whereas vancomycin was mainly prescribed for phlebitis and thrombophlebitis (20%). Therapeutic outcomes indicated that 50% of meropenem patients improved, but 41.25% died, while 60% of vancomycin patients showed improvement. Meropenem was primarily used for empirical therapy (53.75%) for 1–14 days, while vancomycin was mostly used for definitive therapy (80%) with more varied durations, including >14 days (20%). Adverse effects were minimal, with 1 case reported for meropenem (1.25%) and none for vancomycin. This study highlights the importance of rational antibiotic use monitoring to prevent resistance and improve therapeutic effectiveness in hospitals. Keywords: antibiotics, meropenem, vancomycin, bacterial resistance, teaching hospital.